Toy Collections as Symbolic Consumption: A Phenomenological Approach From The Perspective of Islamic Economics - Muchtar, Evan Hamzah (Imara: Jurnal Riset Ekonomi Islam, 2025)
Background. The growing trend of toy collecting by adults reflects symbolic consumption rooted in nostalgia, personal identity, and emotional expression. In the Islamic context, this practice raises ethical considerations about moderation and responsible ownership.Purpose. This study explores how adult Muslim collectors interpret toy collecting as a meaningful practice, assessing its alignment with Islamic economic values such as wasatiyyah (moderation), spiritual intent, and social responsibility.Method. Using a phenomenological approach and narrative analysis, the research draws from digital sources—YouTube, Instagram, Reddit, and TikTok—focusing on narratives related to nostalgia, identity, and financial ethics.Results. Findings reveal that toy collecting can serve as a tool for self-reflection, emotional stability, and spiritual expression when conducted with ethical awareness. However, without boundaries, it risks becoming impulsive consumption (israf).Conclusion. Toy collecting, as a form of symbolic consumption, can align with Islamic principles if guided by intentionality, financial discipline, and social awareness. Enhancing Islamic economic literacy among collectors is essential to ensure meaningful and ethically sound practices.